2018
DOI: 10.1016/j.drugpo.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Service providers’ adherence to methadone maintenance treatment protocol in China

Abstract: The findings suggest the potential benefits of providing institutional support to MMT providers to enhance their level of adherence to the MMT protocol. Intervention effort is needed to reduce negative attitudes towards PWUD among MMT service providers to achieve greater consistency with best-practice recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Regarding health care, a previous study in MMT service found that patients without support had lower adherence rate compared with those with support. Our result was in line with other studies, which showed that positive support from MMT providers could increase adherence [39,40].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding health care, a previous study in MMT service found that patients without support had lower adherence rate compared with those with support. Our result was in line with other studies, which showed that positive support from MMT providers could increase adherence [39,40].…”
Section: Discussionsupporting
confidence: 93%
“…In their research the discontinuation rate was 22% which is lesser than other similar studies, which reported values ranging from 46% to 65%; the authors stated that this is thanks to the absence of troublesome legislations regarding therapeutic services. 16 In the before mentioned study performed by Lin et al, 14 21.5% of the prescribers reported that they found out the reason for patients' treatment cessation through counseling, but the reasons were not explained in the mentioned article.…”
Section: Discussionmentioning
confidence: 98%
“…Thirdly, a linear mixed model was built to examine the adjusted association between the stigma score and other selected variables, in which the province and clinic unit were treated as random-effects factors. We selected the independent variables of the model based on our prior knowledge about potential factors associated with service providers' stigma towards PWUD (Haug et al, 2016;Li et al, 2015;Lin et al, 2018;Ronzani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For people who are addicted to substances, prejudicial attitudes and stereotypes from service providers may weaken their willingness to access healthcare, hinder adherence to treatment, and compromise health outcomes (Borders, Booth, & Curran, 2015;Chakrapani, Velayudham, Shunmugam, Newman, & Dubrow, 2014;Mburu et al, 2018). For service providers, their negative attitudes to PWUD may decrease their interaction with patients and reduce adherence to treatment protocols (Li, Wu, Cao, & Zhang, 2012;Lin, Lan, Li, & Rou, 2018). Meanwhile, the occupational burnout and fatigue of service providers may be increased as a result of working with stigmatized groups (Haug, Bielenberg, Linder, & Lembke, 2016;Morgan, Lee, & Sebar, 2015).…”
Section: Introductionmentioning
confidence: 99%